hsa_circ_0129047 Upregulates LYVE1 to Inhibit Hepatocellular Carcinoma Progression by Sponging miR-492 - Feng, Zhenzhen; Wu, Jiyuan (Disease Markers, 2023)
Compelling evidence indicates the regulatory role of circular RNAs in cancers, including hepatocellular carcinoma (HCC). Our study aimed to elucidate the regulatory function of circ_0129047 in HCC progression. A reverse transcription-quantitative polymeric chain reaction was conducted to detect the expression of circ_0129047, lymphatic vessel endothelial hyaluronan receptor-1 (LYVE1), and miR-492 in HCC tissues and cells. The characteristics of circ_0129047 were determined by evaluating the nuclear and cytoplasmic fractions and by RNase R digestion assays. The cell counting kit-8 assay, scratch wound, and transwell invasion assays were used to examine the effects of circ_0129047 overexpression, miR-492 mimic, and LYVE1 overexpression on the proliferation, migration, and invasion abilities of HCC cells in vitro. A mouse xenograft model was also established. The relationship between miR-492 and circ_0129047 or LYVE1 was clarified using luciferase reporter and Argonaute-2 RNA immunoprecipitation assays. We found that circ_0129047 and LYVE1 were poorly expressed in HCC tissues and cells, whereas miR-492 was upregulated. Overexpression of circ_0129047 inhibits HCC cell proliferation, migration, and invasion and delays in vivo tumor growth. Furthermore, circ_0129047 sponged miR-492, and 3′UTR LYVE1 was a direct target of miR-492. Additionally, LYVE1 overexpression reduced the oncogenic activity of the miR-492 mimic, whereas the miR-492 mimic abolished the antimigratory, antiproliferative, and anti-invasive effects of circ_0129047 overexpression in HCC cells. These data suggest that circ_0129047 exerts a tumor-suppressive role in HCC by sponging miR-492 away from LYVE1 and that the circ_0129047/miR-492/LYVE1 axis may be a promising target for HCC treatment.